Polish Independent Press Review, no. 2 (1987) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). A New Initiative to Coordinate Independent Publications / by Michał KołodziejA recent report by the Social Council for Independent Publications described the Independent publishing movement as a means by which various groups in Poland maintain their identity. New Tactics of Repression / by Anna PomianUnder the new legislative procedure introduced at the end of 1986, certain political offenses that were previously punishable by imprisonment will now be penalized by fines and confiscations. The aim of the new policy seems to be to destroy the opposition's material base. Publisher! Insure Your Property! / by Nika KrzeczunowiczThe Warsaw Solidarity weekly, "Tygodnik Mazowsze" [no. 196 (27 January 1987)], published an interview with a representative of the Independent Publishers' Insurance Fund on covering losses resulting from repression directed against underground publications. Psychological Destabilization of Society / by Nika KrzeczunowiczThe bimonthly "Obraz" [Picture], appearing in Szczecin, printed a study of the various means used by the authorities to blacken the commonly perceived image of reality in Poland. Afghanistan: Polish Views and Hopes / by Anna PomianPolish support for the resistance in Afghanistan has included medical aid, demonstrations of solidarity, and commemorative leaflets and articles, as well as extensive documentation in the independent press. The scope of coverage has recently increased as a result of the seventh anniversary of the invasion of Afghanistan and the hope that the fighting will soon come to an end. Let's Wish Each Other Good Health / by Nika KrzeczunowiczThe bimonthly "Obraz" [Picture], [no. 8/9(39/40) (August/September 1986)] appearing in Szczecin, offers a few personal glimpses of the notoriously bad state of Polish healthcare, as exemplified by hospitals.